A Global Perspective on Machine Translation: Arabic as a Case Study - Al-Assadi, Wesam (2004)
A Master of Arts Thesis Submitted to the Department of English & Translation Studies by Wessam Al - Assadi, "A Global Perspective on Machine Translation: Arabic as a Case Study," May 11, 2004. Advisor Dr. Rana Raddawi. Thesis available only in hard copy in Reference and AUS Archives